Myofibroma in the Palm Presenting with Median Nerve Compression Symptoms - Heidi Sarkozy, PA-C, BS (Plastic and Reconstructive Surgery, Global Open, 2014)
Summary: A myofibroma is a benign proliferation of myofibroblasts in the connective tissue. Solitary myofibromas are a rare finding especially in an adult. We report a case of a 23-year-old man presenting with an enlarging mass over his right palm. The patient is an active weight lifter. He reported numbness and tingling in the median nerve distribution. Nerve conduction studies and magnetic resonance imaging scans suggested a tumor involving or compressing the median nerve. The final diagnosis of myofibroma was made only after the histopathological diagnosis.